RRGNNV capsid protein amino acids 247 and 270 are involved in betanodavirus virulence to European sea bass (Dicentrarchus labrax) - Moreno, Patricia; Souto, Sandra; Leiva-Rebollo, Rocío; García-Rosado, Esther; Borrego-García, Juan José; Bandín Matos, Isabel; Alonso-Sánchez, María del Carmen (My University, 2019)
Recombinant RGNNV viruses harbouring SJNNV-type amino acids at positions 247 and/or 270 (Mut247Dl965, Mut270Dl965, Mut247+270Dl965) were generated by reverse genetics. The effect of these modifications on viral replication was evaluated in cell culture andin infected fish. Experimental infections were also performed to analyse viral virulence and fish immune response.
Keywords: Luvinas-Virus; Virología veterinaria; Microbiología; RGNNV; European sea bass; Reverse genetics; Betanodvirus; Virulence